2018
DOI: 10.1038/s41380-018-0017-5
|View full text |Cite
|
Sign up to set email alerts
|

Depression and obesity: evidence of shared biological mechanisms

Abstract: Depression and obesity are common conditions with major public health implications that tend to co-occur within individuals. The relationship between these conditions is bidirectional: the presence of one increases the risk for developing the other. It has thus become crucial to gain a better understanding of the mechanisms responsible for the intertwined downward physiological spirals associated with both conditions. The present review focuses specifically on shared biological pathways that may mechanisticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
532
3
21

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 696 publications
(574 citation statements)
references
References 184 publications
18
532
3
21
Order By: Relevance
“…In addition, the pleiotropic risk loci were enriched among genes previously associated with neuroticism (corrected enrichment p= 5.28x10 -6 ; GRIK3, CTNND1,DRD2,RGS6,RBFOX1,ZNF804A,L3MBTL2,CHADL,RANGAP1,RSRC1,GRM3), cognitive ability (corrected p= 7.15x10 -5 ; PTPRF, NEGR1, ELOVL3, SORCS3, DCC, CACNA1I), and night sleep phenotypes (corrected p= 1.86x10 -2 ; PBX1, NPAS3, RGS6,GRIN2A,MYO18A,TIAF1,CNTN4,PPP2R2B,TENM2,CSMD1). We also found significant enrichment of pleiotropic risk genes in multiple measures of body mass index (BMI), supporting previous studies suggesting a shared etiologic basis between a range of neuropsychiatric disorders and obesity (Hartwig et al, 2016;Lopresti and Drummond, 2013;Milaneschi et al, 2018)…”
Section: Relationship Between Cross-disorder Genetic Risk and Other Bsupporting
confidence: 89%
“…In addition, the pleiotropic risk loci were enriched among genes previously associated with neuroticism (corrected enrichment p= 5.28x10 -6 ; GRIK3, CTNND1,DRD2,RGS6,RBFOX1,ZNF804A,L3MBTL2,CHADL,RANGAP1,RSRC1,GRM3), cognitive ability (corrected p= 7.15x10 -5 ; PTPRF, NEGR1, ELOVL3, SORCS3, DCC, CACNA1I), and night sleep phenotypes (corrected p= 1.86x10 -2 ; PBX1, NPAS3, RGS6,GRIN2A,MYO18A,TIAF1,CNTN4,PPP2R2B,TENM2,CSMD1). We also found significant enrichment of pleiotropic risk genes in multiple measures of body mass index (BMI), supporting previous studies suggesting a shared etiologic basis between a range of neuropsychiatric disorders and obesity (Hartwig et al, 2016;Lopresti and Drummond, 2013;Milaneschi et al, 2018)…”
Section: Relationship Between Cross-disorder Genetic Risk and Other Bsupporting
confidence: 89%
“…Looking at specific QTL, we identified the genes Insig2 and Ksr2 on the highest point in the region for the class Mollicutes (chr1:121,315,223, LOD = 7.002) and the order Bacteroidales (chr5:117,733,508, LOD = 7.203) respectively. INSIG2 plays a central role in the pathway by which the circadian clock regulates liver lipid metabolism and Ksr2 has been implicated in being associated with BMI and severe early-onset obesity through large scale GWAS studies [Milaneschi et al 2019].…”
Section: Qtl Mappingmentioning
confidence: 99%
“…Yet, intervention studies showed that a plant-based vegan diet compared to a conventional omnivorous diet reduced anxiety and depression or emotional distress 1922 , proposing that restricting animal-based products per se may not affect mental health, but rather exert beneficial effects. Notably, we observed that different personality traits and BMI predicted depressive symptom score, which hints towards shared neurobiological mechanisms with obesity 23,25 . These shared mechanisms might help to explain previous inconsistent findings of a proposed link between restrictive diets and depression: certain personality traits may increase the probability to restrict certain food groups from diet, such as openness and conscientiousness 59 .…”
Section: Discussionmentioning
confidence: 54%
“…In addition, both weight gain and weight loss may relate to depressive symptoms 23 , and obesity and depression are assumed to share not only certain symptoms but also genetic pathways and personality traits, in particular neuroticism (reviewed in 24 ). For example, studies showed that higher neuroticism and lower conscientiousness correlate with a higher BMI and more depressive symptoms 25,26 . Moreover, differences in personality traits and demographic factors such as age, sex and education have also been linked to more or less restrictive lifestyle habits, including diet 27–29 .…”
Section: Introductionmentioning
confidence: 99%